A Construction of Mirror 𝑄-Algebras - Keum Sook So (International Journal of Mathematics and Mathematical Sciences)
We investigate how to construct mirror 𝑄-algebras of a 𝑄-algebra, and we obtain the necessary conditions for 𝑀(𝑋) to be a 𝑄-algebra.